A Monodisperse Rh2P‐Based Electrocatalyst for Highly Efficient and pH‐Universal Hydrogen Evolution Reaction. Issue 18 (24th March 2018) - Yang, Fulin; Zhao, Yuanmeng; Du, Yeshuang; Chen, Yongting; Cheng, Gongzhen; Chen, Shengli; Luo, Wei
Abstract: The search for Pt‐free electrocatalysts exceeding pH‐universal hydrogen evolution reaction (HER) activities when compared to the state‐of‐the‐art commercial Pt/C is highly desirable for the development of renewable energy conversion systems but still remains a huge challenge. Here a colloidal synthesis of monodisperse Rh2 P nanoparticles with an average size of 2.8 nm and their superior catalytic activities for pH‐universal HER are reported. Significantly, the Rh2 P catalyst displays remarkable HER performance with overpotentials of 14, 30, and 38 mV to achieve 10 mA cm −2 in 0.5m H2 SO4, 1.0m KOH, and 1.0m phosphate‐buffered saline, respectively, exceeding almost all the documented electrocatalysts, including the commercial 20 wt% Pt/C. Density functional theory calculations reveal that the introduction of P into Rh can weaken the H adsorption strength of Rh2 P to nearly zero, beneficial for boosting HER performance. Abstract : 2.8 nm monodisperse Rh2 P nanoparticles with narrow size distribution are synthesized through a one‐pot hot solution colloidal synthetic route and further used as remarkable catalysts for pH‐universal hydrogen evolution reaction (HER). The enhanced HER performance is attributed to the introduction of P into Rh, which resulting in the optimized free energy of hydrogen adsorption.